SOSIALISASI DAN PENDAMPINGAN MASYARAKAT DALAM MEMAJUKAN EKOWISATA WADUK KOTA LHOKSEUMAWE - maryana, maryana; Hikalmi, Hikalmi; Miswar, Miswar; Fauzan, Fauzan; Zularnaini, Zulkarnaini (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2024)
The city of Lhokseumawe is famous for its rows of beautiful and exotic beaches, one of which is the Pusong Reservoir tourist attraction. Pusong Reservoir is a water reservoir that has a very aesthetic charm, because it is located next to the ocean and has many shady trees. However, this beach is experiencing quite serious problems with lots of rubbish strewn around and causing a foul smell. Cleanliness of the beach area from rubbish is the main requirement so that tourists are comfortable and at home enjoying the beauty of nature, For this reason, the waste problem requires serious handling, especially raising awareness among the people who live around the Pusong Reservoir. To overcome this problem, the PKM team carried out outreach and assistance to communities directly related to the existence of the Pusong reservoir. The results of this PKM show that ways and steps in building and increasing awareness and concern for environmental cleanliness need to be carried out to build synergy because this factor can influence public awareness.